1993
DOI: 10.1111/j.1528-1157.1993.tb02110.x
|View full text |Cite
|
Sign up to set email alerts
|

Corpus Callosotomy for Intractable Epilepsy: Seizure Outcome and Prognostic Factors

Abstract: We reviewed the outcome of corpus callosal section in 64 adult and pediatric patients to identify factors associated with a good outcome: 48% of patients had a favorable outcome for overall seizure frequency. Improvement was noted in several seizure types and was most likely for drop attacks, particularly in the setting of a unilateral focal cerebral lesion or a true generalized epilepsy of Lennox-Gastaut type. Poor outcomes for drop attacks were more likely if there was associated severe intellectual handicap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
51
2
4

Year Published

2001
2001
2017
2017

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(63 citation statements)
references
References 12 publications
(20 reference statements)
6
51
2
4
Order By: Relevance
“…One area of consensus for the use of complete corpus callosotomy does exist. Many support the belief that complete callosotomy is preferable for atonic seizure (drop attacks) with results that are superior to those of partial sectioning [20,21,22]. At our institution we favor the use of complete callosotomy since we have found that it provides excellent seizure control with minimal morbidity when the procedure is performed in children.…”
Section: Discussionmentioning
confidence: 89%
“…One area of consensus for the use of complete corpus callosotomy does exist. Many support the belief that complete callosotomy is preferable for atonic seizure (drop attacks) with results that are superior to those of partial sectioning [20,21,22]. At our institution we favor the use of complete callosotomy since we have found that it provides excellent seizure control with minimal morbidity when the procedure is performed in children.…”
Section: Discussionmentioning
confidence: 89%
“…Favorable outcome as more than 50% reduction in seizures was noted in generalized tonic-clonic seizures (38-86%), generalized tonic seizures (43-60%), atonic seizures (60-83%) and complex partial seizures (50-51%). (Fuiks, Wyler et al 1991;Oguni, Olivier et al 1991;Reutens, Bye et al 1993) Our data shows 35% seizure free rates in total. 76.4 % showed significant improvement after surgery and drop attacks was the seizure type with most effective result (91.2%).…”
Section: Outcomementioning
confidence: 99%
“…In patients with drug-resistant epilepsy, the chance of achieving seizure freedom with subsequent antiepileptic drug treatments is modest [1] . Compared with other palliative treatments [2][3][4] such as vagus nerve stimulation (VNS) and deep brain stimulation (DBS), conventional open surgery is a better treatment option [5,6] .…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to other palliative [2,3] treatments such as vagus nerve stimulation (30%-63% reduction of >50% of seizures) [4][5][6] , multiple subpial transection [32] , callosotomy [33] , or deep brain stimulation of the anterior nucleus of the thalamus (54% reduction of >50% of seizures) [6] , SEEG-guided RF-TC is a focal treatment targeted selectively at the epileptogenic zone (as is radiosurgery) [34,35] . Furthermore, SEEG-guided RF-TC efficacy is a predictor of outcome in patients who undergo conventional open surgery [17] .…”
Section: Introductionmentioning
confidence: 99%